Pyoderma gangrenosum as a initial manifestation of ulcerative proctocolitis - Fonseca,Carla Bortolin (2011)
pyoderma gangrenosum is a rare inflammatory skin condition characterized by progressive and recurrent skin ulceration of destructive course. It is usually associated with rheumatoid arthritis, paraproteinemia, myeloproliferative diseases and inflammatory bowel diseases, especially non-specific ulcerative proctocolitis. In these situations, skin lesions are described as concurrent with the intestinal condition. However, reports on pyoderma gangrenosum preceding intestinal findings are less frequent. The authors describe a case of a woman with febrile condition associated with skin lesions diagnosed by biopsy as pyoderma gangrenosum. Two weeks later, she developed diarrhea, arthralgia and sepsis, being diagnosed as ulcerative proctocolitis. After the administration of the treatment for ulcerative proctocolitis, she showed improvements in sepsis care, remission of diarrhea and regression of skin lesions. This case highlights the importance of considering pyoderma gangrenosum as a manifestation associated with inflammatory bowel disease, regardless of its timing in relation to intestinal symptoms.